Time‐Dependent Density Functional Theory of Narrow Band Gap Semiconductors Using a Screened Range‐Separated Hybrid Functional. Issue 12 (9th November 2020) - Wing, Dahvyd; Neaton, Jeffrey B.; Kronik, Leeor
Abstract: Predicting the band structure and optical absorption spectra of narrow band gap semiconductors is challenging for electronic structure methods. Here, it is shown shown that density functional theory can yield accurate band structures and time‐dependent density functional theory (TDDFT) can yield accurate optical absorption spectra for these systems. This is achieved by using a screened range‐separated hybrid (SRSH) functional with a single empirical parameter, fit to reproduce the experimental band gap. By comparing TDDFT results based on the SRSH approach with those obtained based on the Heyd–Scuseria–Ernzerhof functional it is shown that screened long‐range exact exchange improves the accuracy of the TDDFT spectra for these systems. Abstract : The optical absorption spectra of four narrow band semiconductors—Ge, GaSb, InAs, and InSb—are calculated using time‐dependent density functional theory with a screened range‐separated hybrid functional, where one parameter is fit to reproduce the experimental band gap. The approach is more accurate than a short‐range hybrid functional and the resulting spectra agree well with experiment.